Practical clinical tool to monitor dementia symptoms: the HABC-Monitor - Monahan PO (Dove Medical Press, 2012)
Patrick O Monahan,1 Malaz A Boustani,1–3,6 Catherine Alder,2,3,6 James E Galvin,7 Anthony J Perkins,2,3 Patrick Healey,4 Azita Chehresa,5 Polly Shepard,8 Corby Bubp,8 Amie Frame,2,3 Chris Callahan1–3,61Indiana University School of Medicine, 2Indiana University Center for Aging Research, 3Regenstrief Institute Inc, 4St Vincent’s Health Network, 5Community Health Network, 6Wishard Health Services, Eskenazi Health, Indianapolis IN, 7Alzheimer Disease Center, Departments of Neurology and Psychiatry, New York University School of Medicine, New York, NY, 8Memory Clinic of Indianapolis, Indianapolis, IN, USABackground: Dementia care providers need a clinical assessment tool similar to the blood pressure cuff (sphygmomanometer) used by clinicians and patients for managing hypertension. A “blood pressure cuff” for dementia would be an inexpensive, simple, user-friendly, easily standardized, sensitive to change, and widely available multidomain instrument for providers and informal caregivers to measure severity of dementia symptoms. The purpose of this study was to assess the reliability and validity of the Healthy Aging Brain Care Monitor (HABC-Monitor) for measuring and monitoring the severity of dementia symptoms through caregiver reports.Methods: The first prototype of the HABC-Monitor was developed in collaboration with the Indianapolis Discovery Network for Dementia, which includes 200 members representing 20 disciplines from 20 local organizations, and an expert panel of 22 experts in dementia care and research. The HABC-Monitor has three patient symptom domains (cognitive, functional, behavioral/psychological) and a caregiver quality of life domain. Patients (n = 171) and their informal caregivers (n = 171) were consecutively approached and consented during, or by phone shortly following, a patient’s routine visit to their memory care provider.Results: The HABC-Monitor demonstrated good internal consistency (0.73–0.92); construct validity indicated by correlations with the caregiver-reported Neuropsychiatric Inventory (NPI) total score and NPI caregiver distress score; sensitivity to three-month change compared with NPI “reliable change” groups; and known-groups validity, indicated by significant separation of Mini-Mental Status Examination severity groups and clinical diagnostic groups. Although not designed as a screening study, there was evidence for good operating characteristics, according to area under the receiver-operator curve with respect to gold standard clinical diagnoses, relative to Mini-Mental Status Examination or NPI.Conclusion: The HABC-Monitor demonstrates good reliability and validity as a clinically practical multidimensional tool for monitoring symptoms of dementia through the informal caregiver.Keywords: dementia, symptoms, monitor, validation, cognitive impairment, memory care